We are on the same boat, but still I am from another culture: the lived experiences of learning in groups - Sandra Kaire (University of Bologna, 2017)
What does it mean to learn in a group of people from different cultures? How does one encounter people from different cultures when there is no clear 'quantitative' domination of any culture? By asking these questions the paper represents a hermeneutic phenomenological study that explores the phenomenon of learning in a culturally diverse group. A phenomenological study is undertaken with young people (18-30 years) from different EU countries who participated in learning mobility project European Voluntary Service and had long-term volunteering experience abroad. The research concentrates on the lived moments of vis-à-vis intercultural encounters during learning process in groups. Specifically, through the descriptions of lived experience and phenomenological reflection the paper describes how young people experience self and others while they are learning in culturally diverse groups. Lived experiences of young people lead them into 'no-man's land' (Waldenfels, 2011) where connection and separation simultaneously exist.